Contribution of Buddhist mindfulness to the transformation of conflict - dependent origination (paticca-samuppada and deconstruction of identity - Zalta, Anja (Asian studies, 2016)
The article presents Buddhist mindfulness as a method for conflict transformation. On the basis of the concept of paticca-samupp, da (dependent origination) and anatta (nonself) the article (de)constructs the phases of identity formation. In Buddhist understanding, conflict is the result of defensiveness and misconceptions, and thus it is central to understand the mechanism by which the idea of "I" or "self" is established. The purpose of mindfulness is (among other things) to achieve a radical change in perception, which leads to "de-automatization" of mental mechanisms and suspends the identification with sensory and mental experiences that an individual calls a separate "I". Since the Buddhist approach to conflict is based on a theory of cognition, this article emphasizes the individual effort needed for conflict transformation. Only later could or should this knowledge be applicable to a wider social environment, taking into account the diversity of socio-cultural conditions.
Keywords: čuječnost; mindfulness; nasilje; violence; soodvisnost; dependent origination; Buddhism; budizem